Development Of Web-Based Interactive Game Media Application Wordwall Material Odd Numbers Even Mathematics Subjects Grade II Elementary School - Susilo Sudarsono; Sapriya (International Conference on Elementary Education, 2023)
Teaching a new concept in mathematics to students requires more attention from the teacher. That teaching will be very risky if it is not implemented as much as possible so that students are able to understand the new concepts correctly. The concept of odd-even numbers is one of the concepts in mathematical numbers and is often taught with less attention and seems sober to finally make students less understanding of the concept. The purpose of this study is to develop a web-based interactive game learning media wordwall application in mathematics subjects the concept of odd-even numbers for the second grade of elementary school. The research uses the ADDIE development method which has five stages of research, namely analysis, design, development, implementation, evaluation. Learning media was declared feasible from the validation results of media experts with a percentage of 87.5% and material experts with a percentage of 88% and questionnaires filled by students with 97%, in addition to tu there was also an increase in test scores in limited trials from an average pre-test score of 75 to an average post-test score of 95.